Decision Support System of Achieving Student Using Weighted Product Method - R. Mohamed, Rajina; A. Mohamed, Mohamad; Rahayu, Dewi; Hashim, Wahidah; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2019)
Higher education as part of the national education system that has a strategic role in educating the life of the nation. Students are people who are trying to develop themselves through the process of education on the path, level and type of education. The Weigted Product (WP) method was chosen because the method is solved by using multiplication to connect the value of the attribute, where the value must be raised with the attribute weight value in question. Criteria criteria that have been determined include: average value, discipline, attendance, extracurricular, and Non-Academic. The results of this study there were 6 alternatives, that alternative student with a value = 0.145790734 as a student with the lowest and alternative value Diamond = 0.212196782 as the student with the best value